Contribution of rivaroxaban to the international normalized ratio when switching to warfarin for anticoagulation as determined by simulation studies - Siegmund, Hans-Ulrich (Br J Clin Pharmacol, 2015)
AIM: This study evaluated the influence of rivaroxaban 20 mg once daily on international normalized ratio (INR) during the co-administration period when switching from rivaroxaban to warfarin. METHODS: We developed a calibrated coagulation model that was qualified with phase I clinical data. Prothrombin time and INR values were simulated by use of phospholipid concentrations that matched Neoplastin Plus® and Innovin® reagents. To simulate the combined effects of rivaroxaban and warfarin on INR during switching, warfarin initiation was simulated by adjusting the magnitude of the warfarin effect to reach the desired target INRs over the course of 21 days. The warfarin effect values (obtained every 6 h) and the desired rivaroxaban plasma concentrations were used. Nomograms were generated from rivaroxaban induced increases in INR. RESULTS: The simulation had good prediction quality. Rivaroxaban induced increases in the total INR from the warfarin attributed INR were seen, which increased with rivaroxaban plasma concentration. When the warfarin only INR was 2.0–3.0, the INR contribution of rivaroxaban with Neoplastin Plus® was 0.5–1.2, decreasing to 0.3–0.6 with Innovin® at median trough rivaroxaban plasma concentrations (38 μg l(−1)). CONCLUSIONS: The data indicate that measuring warfarin induced changes in INR are best performed at trough rivaroxaban concentrations (24 h after rivaroxaban dosing) during the co-administration period when switching from rivaroxaban to warfarin. Furthermore, Innovin® is preferable to Neoplastin Plus® because of its substantially lower sensitivity to rivaroxaban, thereby reducing the influence of rivaroxaban on the measured INR.